Canada's Cannabis Legalization with Strict Public Health Control Lessons for Germany? - Rehm J. (2023)
Aims: To describe the impact of the legalization of cannabis for recreational use under strict public health control in 2018 on the following outcomes: cannabis use and use patterns, attributable harm, economic considerations. Methodology: Narrative review based on government documents, surveys, and published literature. Results: The 12-month prevalence increased after legalization and has decreased during the COVID-19 pandemic. Little change in prevalence for adolescents. Persons with daily use remained stable. No rigorous studies on changes in attributable health harm, but some indication that harm, as measured in prevalence of cannabis use disorders, treatment rate, and attributable traffic injury remained stable. No data yet available for cancer. Cannabis attributable emergency visits increased, including among children (poisoning). Cannabis-related offences decreased as biggest public health gain. Economic predictions were not realized, and there is some pressure from cannabis industry to loosen public health regulations in order to increase use. Conclusions: Overall, while not achieving its main objectives of more youth protection and decreases in cannabis-attributable health harm, legalization with strict public health control resulted in less cannabis-related offences and up to now did not seem to increase cannabis-attributable disease burden.